The two-directional prospective association between inflammatory bowel disease and neurodegenerative disorders: a systematic review and meta-analysis based on longitudinal studies - Zong, Jiahao; Yang, Yue; Wang, Hui; Zhang, Huipeng; Yang, Xiaorong; Yang, Xiaoyun (Frontiers in Immunology, 2024)
Objective Previous studies reported possible connections between inflammatory bowel disease (IBD) and several neurodegenerative disorders. However, the comprehensive relationships between IBD and various neurodegenerative disorders were not summarized. We executed a meta-analysis of longitudinal studies to provide an estimate of the strength of the two-directional prospective association between IBD and neurodegenerative disorders. Methods We accomplished a thorough bibliographic search of PubMed, Web of Science, Embase, PsycINFO, and Cochrane Library databases until June 2023 to locate relevant longitudinal studies. The extracted data were then analyzed via meta-analysis using either a fixed or random effects model. Results The final analysis encompassed 27 studies. Individuals with IBD faced an increased risk of developing four neurodegenerative disorders than the general public, namely, Alzheimer’s disease (hazard ratio[HR] = 1.35, 95% confidence interval [CI]: 1.03–1.77, P=0.031), dementia (HR =1.24, 95% CI: 1.13–1.36, P<0.001), multiple sclerosis (HR =2.07, 95% CI:1.42–3.02, P<0.001) and Parkinson’s disease (HR =1.23, 95% CI:1.10–1.38, P<0.001). Two articles reported an increased incidence of amyotrophic lateral sclerosis or multiple system atrophy in IBD patients. Three studies investigated the prospective association between multiple sclerosis and IBD, revealing an elevated risk of the latter in patients with the former. (HR=1.87, 95% CI:1.66–2.10, P<0.001). Interpretation These findings verified the two-directional relationship between the brain-gut axis, specifically demonstrating a heightened risk of various neurodegenerative diseases among IBD patients. It may be profitable to prepare screening strategies for IBD patients to find neurodegenerative diseases during the long-term course of treatment for IBD with a view to potential earlier diagnosis and treatment of neurodegenerative diseases, reducing public health and social burden.